A Educação Intergeracional como Tecnologia Social: uma vivência no âmbito da Universidade da Maturidade - UFT - Costa, Samara Queiroga Borges Gomes da (Universidade Federal do Tocantins, 2017)
Life expectancy is increasing in the majority of countries and there is concern in the societies about solving the challenges associated with this fact. In this context there is the school, which possesses the task of forming citizens capable of understanding both the diversity in which they are involved in the social sphere and the relevance of respecting the different generations, according with their specific characters, based upon the social and cultural changes that arise over the years. This situation brings up the question: how to enable an interaction among generations aimed at social inclusion during the children‟s learning process in which the concept of aging could be internalized? In view of such question, this research seeks to show the role of the intergenerational education as social technology and its functionality as an instrument for the development of pedagogical actions that can integrate generations and enable the development of subjects committed with the transformation of society. This was made based mainly in the following theorists: Pesce (2013), Andery (2012), Santos (2010), Kuhn (2000), Chizzotti (2006), Rezende (1990), Merleau-Ponty (2001); Vygostky (1999), Beauvoir (1976), Groisman (1999), Rego (1995), Strauss e Howe (1992), McCrindle (2009), Lombardia (2008), Debert (2006); Lèvy (1999), Sassaki (1997), Valadão et al (2014), Carvalho (1997) De Paulo (2004). The use of intergenerational education as social technology enables transformations in which the children can understand that older individuals doesn‟t have a secondary role in society. To teach the specific characters of the generations with intergenerational activities developed by means of inter- and transdisciplinarity will enable to the children a kind of development that generates transformation and thus, the formation of individuals who understand the differences of the society in which they are involved and who can therefore respect the others, reducing intergenerational conflicts.